Genetic entanglement between Cercospora species associating soybean purple seed stain - Guillin, Eduardo Alejandro (2017)
Soybean purple seed stain (S-PSS) is a destructive, worldwide distributed fungal disease caused by several Cercospora species. This work aims to shed light on the nature of the genealogical and genetic relationships amongst S-PSS causal agents. Fungal isolates were obtained from Argentina and Brazil, which belong to the leading countries in soybean production worldwide. DNA sequences were obtained from eight loci across the collection of isolates. Relationships were evaluated through Bayesian phylogenetic inferences, and distance and character-based network analyses and discriminant analyses. The occurrence of reticulate evolutionary events was tested with recombination tests. The high haplotype diversity (H = 1.0) was arranged in four validated haplogroups. Reticulate network topologies were evident, and 11 recombination events were validated through several tests. Five of these events occurred across species boundaries. Comparison with sequences from 70 Cercospora species indicated that at least five monophyletic groups of S-PSS-causing agents are currently present in South America. The provided evidence supports the hypothesis that interspecific genetic exchange plays a significant role in the evolutionary dynamics of Cercospora species in this region. The occurrence of interspecific recombination has implications for understanding epidemiological threats to soybean production that appear to be more serious than previously anticipated.